Ponorogo Regency Regional Government's Readiness In Digitalizing The Management Of Parking Fees On The Side Of Public Roads - saputri, Redya wulan; Purnomo, Rochmat Aldy; Cahyono, Yeni; Asis Riat Winanto; Choirul Hamidah (Jurnal Ekonomi, 2024)
Parking is a basic need for society related to mobility, and parking fees play an important role in increasing regional income. One way for Regional Governments to improve economic status through local original income is to continue to innovate. This research uses a qualitative method with a case study approach, focusing on the digitization of public roadside parking on Jalan Hos Cokrominoto, Ponorogo Regency. Secondary Data and Primary Data are used to analyze the implementation of the electronic parking system carried out by the Ponorogo Regency Government to increase efficiency and regional income. Despite facing challenges, the successful implementation of this policy is supported by clear regulations. It is hoped that the research results can provide new insights for related parties in efforts to increase local revenue through parking policy innovation.